From re-viewers to me-viewers: The #Bookstagram review sphere on Instagram and the uses of the perceived platform and genre affordances. Issue 1 (1st July 2019) - Jaakkola, Maarit
This study looks at the emerging forms of reviewing cultural products by investigating #bookreviews on Instagram. The multiple-case study focuses on characteristics of book-review posts in global and national contexts. First, the global community is outlined, with the help of quantitative data (N = 163, 269 entries). Second, a local book-reviewing community (N = 645 entries) is studied, with a thematic analysis of platform and genre affordances. Instagram-native formats identified include textual reviews, metacoverage of reviews, video reviews, reviews with visual effects and facilitated reviews. The findings have implications for the conceptualization of user-generated reviewing as part of cultural critique, which requires the incorporation of the consumption/prosumption paradigm into the understandings of cultural intermediation.